Czech and Slovak cinema : theme and tradition - Hames, Peter (Traditions in world cinema., 2009)
This book is the first study in English to examine some of the key themes and traditions of Czech and Slovak cinema, linking inter-war and post-war cinemas together with developments in the post-Communist period. It examines links between theme, genre, and visual style, and looks at the ways in which a range of styles and traditions has extended across different historical periods and political regimes. Czech and Slovak Cinema provides a unique study of areas of Central European film history that have not previously been examined in English. Key Features*An overview of the development of the C.